Investigation of the effect of extrusion process parameters and filler loading on the performance of LDPE composites reinforced with eggshell powder - Yasith S. Perera; Mohammad Naaib; Nisal Ariyasinghe; Chamil Abeykoon (Composites Part C: Open Access)
Eggshells are a household waste material that contributes to landfill waste. Polymer composites reinforced with eggshell powder can be produced in large scale with melt blending using twin-screw extrusion, which can aid in reducing eggshell waste. Proper selection of extrusion parameters and filler loading is crucial in achieving composites with desired performance while optimising the extrusion process. Hence, the aim of this study is to investigate the effect of extruder parameters and filler loading on the mechanical, thermal, and rheological properties of low-density polyethylene (LDPE) composites reinforced with eggshell powder, and motor power consumption of the extruder, which should aid in optimising the melt blending process. Composites were produced with three different filler fractions (i.e., 4 wt.%, 8 wt.%, and 12 wt.%), and extruded under three different temperature settings (i.e., low: 160–200 °C, medium: 170–210 °C, and high: 180–220 °C) and three screw speed settings (i.e., 100, 150, and 200 rpm). Injection moulding was used to produce the tensile specimens for mechanical testing using the composite pellets manufactured via melt blending. The motor power consumption of the extruder rose as the screw speed increased and declined as the set temperatures of the barrel heaters increased. The results confirmed that incorporating eggshell powder as a filler led to a slight increase in the extruder's motor power consumption. Scanning electron microscopy results showed non-uniform dispersion of the filler with increasing filler content. The tensile performance of the composites was influenced by both extruder parameters and filler loading. The inclusion of the filler resulted in enhanced stiffness but compromised the ultimate tensile strength. Rheology test results exhibited a reduction in the storage and loss moduli as well as the complex viscosity due to the incorporation of eggshell powder filler. These properties were significantly influenced by the extrusion process parameters as well. However, the influence of extruder parameters and filler loading on the thermal properties of the composites was found to be negligible. This shows that the filler did not significantly disrupt or promote the nucleation and growth of crystalline regions in the LDPE matrix. It was found that, to obtain high tensile properties while retaining good rheological properties, composites with high filler contents of 8–12 wt.% should be processed at a high screw speed of 200 rpm at low set temperature conditions. Overall, the findings of this study indicate that the produced composites could be utilised for applications that require high stiffness. Furthermore, large-scale production of these composites could provide a long-term solution to the eggshell waste problem.